Solving Problems in Genetics - Kowles, Richard V (Sringer, 2001)
The strategy is to provide the student with the essential steps and the reasoning involved in conducting the analysis, and throughout the book, an attempt is made to present a balanced account of genetics. Any student taking a genetics course will find this an invaluable aid to achieving a good understanding of genetic principles and practice.